A strategy for enhancing girls' attitudes towards professional careers in the mining industry. - Somerville Brown, Carolyn M. (Curtin University, 1999)
The problem addressed in the study concerned the lack of attraction of girls into professional Mining Industry (MI) careers. The study had four main objectives. The first was to review the literature to determine the reasons why there were so few women currently in MI careers, and then to describe strategies that have been successfully used to increase their participation. It quickly became apparent that while little research could be located relating directly to MI, the broader fields of science, engineering and technology (SET) could be reviewed to include the subset of mining-related careers.The second objective was to determine the attitudes towards MI careers of a select group of Year 10 schoolgirls, with the ability to proceed to the tertiary prerequisites for MI courses. This was accomplished through the development, implementation and statistical analysis of an instrument, the Mining Industry Attitude Survey (MIAS), designed specifically to focus on MI-related careers, rather than SET generally.The third objective was to develop and implement appropriate intervention strategies aimed at enhancing the attitudes of the group of girls, as determined through analyses of MIAS and related research. Under the auspices of the Western Australian School of Mines Engineering and Technology Camp, conducted annually in Kalgoorlie, a program of strategies was adapted and implemented over a period of five days at the residential camp.The final objective of the study was to determine if the intervention program did, in fact, enhance participating girls' attitudes. Using quasi-experimental research methods, quantitative data were collected and analysed from girls attending the camp, as the experimental group, and from applicants that did not attend as the control group. In addition, qualitative data were collected from select girls in the experimental group, during the camp program.The outcomes of the study are set out in terms of the main objectives, culminating in a discussion of the implications which the stated findings pose for researchers, practitioners of equity programs and employers of future MI graduates.